Factors Influencing Innovative Work Behavior among Academicians at Politeknik Tuanku Sultanah Bahiyah, Kulim, Kedah - Zainudin, Zatil Aqmar; Aziz, Anidah; Abdullah, Muhammad Syukri; Zul, Muhammad Zairi (Information Management and Business Review, 2024)
Compared to any other field, the research on the Innovative Work Behaviour (IWB) among academicians has been a neglected area. Therefore, the purpose of this study is to investigate the determinant factors influencing IWB among academicians at Politeknik Tuanku Sultanah Bahiyah (PTSB). Social Exchange Theory (SET) was underpinned to determine the relationship between training, reward, knowledge sharing and IWB. Additionally, this study also included work engagement as a mediating variable in the relationship between training, reward, knowledge sharing and IWB. IWB can be defined as the intentional generation, promotion, and realization of new ideas within a work role, workgroup, or organization. It is important to analyze how these dimensions tend to influence the IWB. Data for this study was collected from 118 academicians at PTSB, Kulim, Kedah and the collected data was analyzed by using Smart-PLS. The findings revealed that two dimensions, which are training and knowledge sharing have a significant relationship with IWB whereas reward has an insignificant relationship with IWB. Furthermore, work engagement was found to be significant in mediating training and knowledge sharing, however, work engagement was found to be insignificant in mediating reward and IWB. As a result, it is suggested for institutions and the Ministry of Higher Education (MoHE) to appropriately apply relevant specific tactics to enhance those components as well as IWB. Future research is suggested to replicate this study to other institutions. Next, it is suggested to test other independent variables and mediating variables to deeply understand other determinants that influence IWB.